Viability of Discrete Event Simulation in the Early Design of Production Systems - Bekk, Michael; Moen, Erik (My University, 2020)
In the manufacturing industry, Discrete Event Simulation (DES) is recognised as a tool utilised in the analysis and optimisation of production systems. The effectiveness of DES, however, depends mainly on the data available from the system which is to be simulated and the quality of this data. This thesis investigates the viability of DES when a production system is in its early design stages with limited data available, and no complete system of which to translate into a virtual model. A case study was conducted where a production system in its early design stages was modelled and analysed by applying DES. Following the case study, the results of the case were analysed and a consensus was formed whether DES was usable as a tool to assist the system developers in the development process. Despite a lack of highquality data, the case produced useful results for the system developers, and a clear trend of the performance and behaviour of the system was observed. Improvement suggestions were passed on to the system developers to assist the developers and as an extension save time and money. With the support of successful case results, substantial proof that DES is viable to use as a design tool in the early design of production systems were found. However, this is not without its challenges, as the majority of the required data and the behaviour of the system has to be estimated, limiting the accuracy of the results. Despite these challenges, DES is a viable approach, and can be utilised to influence design changes and parameter improvements of production systems in their early design stages.
Keywords: discrete event simulation, discrete event systems, case-study, production systems; early design, viability, simulation